(untitled) (Third Sector Social Economic Review, 2025)
Capital structure decisions are one of the most difficult and strategic decisions that businesses make in order to reach the financing they need to continue their activities and sustain their existence, and to decide on the most appropriate capital structure between debt and equity usage levels. These decisions play a much more important role in financing investments in capital-intensive businesses such as the manufacturing sector. The study aims to determine which capital structure theories the firm-specific variables are compatible with, using the quarterly financial data of 137 manufacturing industry companies traded on Borsa Istanbul (BIST) between 2015Q1-2023Q3. In the study where the panel data regression analysis method was used, leverage ratio, short term liabilities /total assets and long-term liabilities /total assets ratios were included in the analysis as dependent variables and 3 separate models were created within the scope of the analysis. When the empirical findings obtained from the models created are examined, a negative and statistically significant relationship at 1% significance level was determined between the dependent variables of return on assets, current ratio, tangible asset ratio, non-debt tax shield and growth rate. On the other hand, it was concluded that the effect of growth potential, firm risk and firm size variables on the leverage ratio was not statistically significant. These findings support the financial pecking order theory from capital structure theories.